Simulation and experimental study of chaos generation in microwave band using Colpitts circuit - Shi, Zhiguo; Ran, Lixin; Chen, Kangsheng (Journal of electronics (China), 2006)
TN4; Chaotic Colpitts circuits with fundamental frequency f* beyond 1GHz are studied by both circuit simulation and experiment using Philips' broadband transistor with threshold frequency of 25GHz. For the basic configuration of Colpitts circuit with f* of about 1.6GHz, broadband continuous power spectra could be obtained from both circuit simulations and experiments. The harmonics of the observed signal from Agilent PSA/ESA spectrum analyzer are as noticeable as far as 12GHz. A modified Colpitts circuit structure employing the parasitic inductance of BJT (Bipolar Junction Transistor) is also proposed and investigated. By circuit simulation, chaotic attractor and broadband continuous power spectra could be obtained from the modified Colpitts circuit with f* of about 3.5GHz. Because the parasitic effects of the prototype board, the experiment result of the modified Colpitts circuit does not agree well with the simulation result. The gap between the simulation and experimental result could be bridged by replacing the lumped circuit elements with distributed ones.